Integration Questions

Question Number 162219 by mathlove last updated on 27/Dec/21

$$\Omega=\underset{\mathrm{0}} {\overset{\mathrm{1}} {\int}}\frac{{log}\left(\mathrm{1}+{x}^{\mathrm{7}} \right)}{\mathrm{1}+{x}^{\mathrm{7}} }{dx}=? \\$$

Answered by amin96 last updated on 27/Dec/21

$$\boldsymbol{{x}}^{\mathrm{7}} =−\boldsymbol{{t}}\:\:\:\:\frac{\boldsymbol{{dt}}}{\boldsymbol{{dx}}}=−\mathrm{7}\boldsymbol{{x}}^{\mathrm{6}} =−\mathrm{7}\boldsymbol{{t}}^{\frac{\mathrm{6}}{\mathrm{7}}} \\$$ $$\Omega=\frac{\mathrm{1}}{\mathrm{7}}\int_{−\mathrm{1}} ^{\mathrm{0}} \frac{{ln}\left(\mathrm{1}−{t}\right)}{\left(\mathrm{1}−{t}\right){t}^{\frac{\mathrm{6}}{\mathrm{7}}} }{dt}=−\frac{\mathrm{1}}{\mathrm{7}}\underset{\boldsymbol{\mathrm{n}}=\mathrm{1}} {\overset{\infty} {\sum}}\boldsymbol{\mathrm{H}}_{\boldsymbol{\mathrm{n}}} \int_{−\mathrm{1}} ^{\mathrm{0}} {t}^{\boldsymbol{\mathrm{n}}−\frac{\mathrm{6}}{\mathrm{7}}} {dt}= \\$$ $$=−\frac{\mathrm{1}}{\mathrm{7}}\underset{\boldsymbol{\mathrm{n}}=\mathrm{1}} {\overset{\infty} {\sum}}\boldsymbol{\mathrm{H}}_{\boldsymbol{\mathrm{n}}} \left[\frac{\boldsymbol{\mathrm{t}}^{\boldsymbol{\mathrm{n}}+\frac{\mathrm{1}}{\mathrm{7}}} }{\boldsymbol{\mathrm{n}}+\frac{\mathrm{1}}{\mathrm{7}}}\right]_{−\mathrm{1}} ^{\mathrm{0}} =−\frac{\mathrm{1}}{\mathrm{7}}\underset{\boldsymbol{\mathrm{n}}=\mathrm{1}} {\overset{\infty} {\sum}}\frac{\boldsymbol{\mathrm{H}}_{\boldsymbol{\mathrm{n}}} \left(−\mathrm{1}\right)^{\boldsymbol{\mathrm{n}}+\frac{\mathrm{1}}{\mathrm{7}}} }{\left(\boldsymbol{\mathrm{n}}+\frac{\mathrm{1}}{\mathrm{7}}\right)}= \\$$ $$=\frac{\mathrm{1}}{\mathrm{7}}\underset{\boldsymbol{\mathrm{n}}=\mathrm{1}} {\overset{\infty} {\sum}}\frac{\boldsymbol{\mathrm{H}}_{\boldsymbol{\mathrm{n}}} \left(−\mathrm{1}\right)^{\boldsymbol{\mathrm{n}}} }{\left(\boldsymbol{\mathrm{n}}+\frac{\mathrm{1}}{\mathrm{7}}\right)}=\underset{\boldsymbol{\mathrm{n}}=\mathrm{1}} {\overset{\infty} {\sum}}\frac{\left(−\mathrm{1}\right)^{\boldsymbol{\mathrm{n}}} \boldsymbol{\mathrm{H}}_{\boldsymbol{\mathrm{n}}} }{\mathrm{7}\boldsymbol{\mathrm{n}}+\mathrm{1}} \\$$

Answered by mindispower last updated on 30/Dec/21

$$\mathrm{1}+{x}^{\mathrm{7}} =\underset{{k}=\mathrm{0}} {\overset{\mathrm{6}} {\prod}}\left({x}−{a}_{{k}} \right),{a}_{{k}} ={e}^{{i}\left(\mathrm{1}+\mathrm{2}{k}\right)\frac{\pi}{\mathrm{7}}} ,{k}\in\left\{\mathrm{0},\mathrm{6}\right\} \\$$ $$\frac{\mathrm{1}}{\mathrm{1}+{x}^{\mathrm{7}} }=\frac{\mathrm{1}}{\mathrm{7}}\underset{{k}=\mathrm{0}} {\overset{\mathrm{6}} {\sum}}\frac{−{a}_{{k}} }{{x}−{a}_{{k}} }. \\$$ $${log}\left(\mathrm{1}+{x}^{\mathrm{7}} \right)=\underset{{j}=\mathrm{0}} {\overset{\mathrm{6}} {\sum}}{ln}\left({x}−{a}_{{j}} \right) \\$$ $$\Leftrightarrow\frac{\mathrm{1}}{\mathrm{7}}\underset{{j}=\mathrm{0}} {\overset{\mathrm{6}} {\sum}}\underset{{k}=\mathrm{0}} {\overset{\mathrm{6}} {\sum}}−{a}_{{k}} \int_{\mathrm{0}} ^{\mathrm{1}} .\frac{{ln}\left({x}−{a}_{{j}} \right)}{{x}−{a}_{{k}} }{dx} \\$$ $$\int_{\mathrm{0}} ^{\mathrm{1}} \frac{{ln}\left({x}−{a}_{{j}} \right)}{{x}−{a}_{{k}} }{dx},{y}={x}−{a}_{{k}} \\$$ $$=\int_{−{a}_{{k}} } ^{\mathrm{1}−{a}_{{k}} } \frac{{ln}\left({y}+{a}_{{k}} −{a}_{{j}} \right)}{{y}}{dy} \\$$ $${y}=\left({a}_{{j}} −{a}_{{k}} \right){z}\Leftrightarrow \\$$ $$\int_{−\frac{{ak}}{{a}_{{j}} −{a}_{{k}} }} ^{\frac{\mathrm{1}−{a}_{{k}} }{{a}_{{j}} −{a}_{{k}} }} \frac{{ln}\left(\left({a}_{{k}} −{a}_{{j}} \right)\left(\mathrm{1}−{z}\right)\right)}{{z}}{dz} \\$$ $$={ln}\left({a}_{{k}} −{a}_{{j}} \right){ln}\left(\mathrm{1}−\frac{\mathrm{1}}{{a}_{{k}} }\right)+\int_{−\frac{{a}_{{k}} }{{a}_{{j}} −{a}_{{k}} }} ^{\frac{\mathrm{1}−{a}_{{k}} }{{a}_{{j}} −{a}_{{k}} }} \frac{{ln}\left(\mathrm{1}−{x}\right)}{{x}}{dx} \\$$ $${Li}_{\mathrm{2}} \left({z}\right)=−\int_{\mathrm{0}} ^{{z}} \frac{{ln}\left(\mathrm{1}−{t}\right)}{{t}}{dt} \\$$ $${We}\:{Get} \\$$ $${ln}\left({a}_{{k}} −{a}_{{j}} \right){ln}\left(\mathrm{1}−\frac{\mathrm{1}}{{a}_{{k}} }\right)+{Li}_{\mathrm{2}} \left(\frac{{a}_{{k}} }{{a}_{{k}} −{a}_{{j}} }\right)−{Li}_{\mathrm{2}} \left(\frac{{a}_{{k}} −\mathrm{1}}{{a}_{{k}} −{a}_{{j}} }\right) \\$$ $${We}\:{Get} \\$$ $$\underset{\mathrm{0}} {\int}^{\mathrm{1}} \frac{{ln}\left(\mathrm{1}+{x}^{\mathrm{7}} \right)}{\mathrm{1}+{x}^{\mathrm{7}} }{dx}=\underset{{j}=\mathrm{0}} {\overset{\mathrm{6}} {\sum}}\underset{{k}=\mathrm{0}} {\overset{\mathrm{6}} {\sum}}\frac{−{a}_{{k}} }{\mathrm{7}}\left[{ln}\left({a}_{{k}} −{a}_{{j}} \right){ln}\left(\mathrm{1}−\frac{\mathrm{1}}{{a}_{{k}} }\right)+{Li}_{\mathrm{2}} \left(\frac{{a}_{{k}} }{{a}_{{k}} −{a}_{{j}} }\right)−{Li}_{\mathrm{2}} \left(\frac{{a}_{{k}} −\mathrm{1}}{\boldsymbol{{a}}_{\boldsymbol{{k}}} −\boldsymbol{{a}}_{\boldsymbol{{j}}} }\right)\right) \\$$